The pampered child syndrome : how to recognize it, how to manage it, and how to avoid it : a guide for parents and professionals - Mamen, Maggie, 1946- (J. Kingsley Publishers, 2005)
The Pampered Child Syndrome is a welcome source of advice for parents or professionals working with children who are given all the love and care they need, yet who remain unhappy, anxious or angry. This book argues that we live in a society where real progress has been made in the development of child-centered parenting, education and care, but that this cultural shift has produced a generation of children who are entitled to the same rights as adults but not ready to accept grown-up responsibil.